Bluffing - German, Harold D.; Akers, Tana; Amarilla, Santiago; Radabaugh, Zach; Weers, Clarissa; Woofter, Jay; Worley, Blaine (My University, 2016)
Credits: Director-Harold Dakota German. Cast-Tana Akers, Santiago Amarilla, Zach Radabaugh, Clarissa Weers, Jay Woofter, Blaine Worley. Music-“Birthday Cake” by Jahazzar, “The Great Avenger” by Silent Partner.
Citation: Team Couch. (2016). Bluffing. K-State 48 Film Festival, 2016
Keywords: Team Couch; K-State 48 Film Festival